2017
DOI: 10.3390/su9081456
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Socio-Economic Factors Affecting Social Sustainability through Impacts on Perceived Health Care Quality and Public Health: The Case of Vietnam

Abstract: A study on over 2000 patients has been conducted in Hanoi, Vietnam, to explore the influences of psychological and socio-economic factors on the evaluation of healthcare quality and public health by patients. The findings suggest effective health communication and the status of being married are two elements that have the strongest impact on people's positive perceptions about healthcare quality (β HealthCom = 0.210, β otherMaritalstt = −0.386, p < 0.001). Young unmarried people and the insured tend to be more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 36 publications
2
20
1
1
Order By: Relevance
“…where ∑ j π j (x) = 1; and there are n observations in the sample, j represents the categorical values of an observation i, and h is a row in the matrix X i . Estimated probabilities can be used to predict the possibilities of Y under different conditions of X i [42,45,47]. The statistical significance of independent variables in the model is determined based on z-value and p-value; with p < 0.05 being the conventional level of statistical significance required for a positive result.…”
Section: Methodsmentioning
confidence: 99%
“…where ∑ j π j (x) = 1; and there are n observations in the sample, j represents the categorical values of an observation i, and h is a row in the matrix X i . Estimated probabilities can be used to predict the possibilities of Y under different conditions of X i [42,45,47]. The statistical significance of independent variables in the model is determined based on z-value and p-value; with p < 0.05 being the conventional level of statistical significance required for a positive result.…”
Section: Methodsmentioning
confidence: 99%
“…The ever-changing lifestyles and conditions have long constituted the importance of not only natural but also social sustainability because health and safety status of people are affected by both environmental and social factors and a community must prioritize the health and safety of its population to sustain itself [35]. Having the focus of majority of previous research on the role of unhealthy environmental factors in sustaining communities, human health also depends on social matters [35].…”
Section: Social Sustainabilitymentioning
confidence: 99%
“…Quality communication, as a form of collaboration, can facilitate the process of sharing information, knowledge, experience, and resources among stakeholders and then this can improve the quality of care and the accessibility of care services for patients. For instance, Vuong et al [35] showed that quality communication provides patients with more medical information, both in quality and quantity, and this results in enhanced user wellbeing. Furthermore, if user needs were explored, the healthcare system would be better able to fulfill them.…”
Section: Collaborative Healthcare and Social Sustainabilitymentioning
confidence: 99%
“…Despite the expansion of investment into mental health research and development of central government in Korea, there was a huge disproportion in directing the investment, with only 10% of the budget [63] is spent on studies of mental health policies, services, and humanities and social sciences issues, etc., while another 90% was spent on basic research, therapy, and diagnosis studies. As the depressive level and healthcare usage are significantly affected by multiple social-cultural-economic aspects [25,[64][65][66][67][68][69][70][71], such disproportionate distribution of investment might result in insufficient depression prevention and treatment among particular populations, such as university students. Re-allocation of the investment is, therefore, essential to protect the mental health of the young generation.…”
Section: Funding Provisionmentioning
confidence: 99%